Effect of Corporate Governance on Corporate Social Responsibility and Firm Values: Empirical Evidence from Manufacturing Companies in Indonesia - Neva Novianti; Siti Rahmi; Zaitul Zaitul (Universitas Batanghari Jambi, 2022)
Corporate governance (CG) and corporate social responsibility (CSR) are no longer voluntary. However, it has become a mandatory for every company, especially in increasing the value of the company, although there are still many pros and cons. This study aims to investigate the effect of CG practices on CSR as well as the influence of CG and CSR on firm value. The object of this research is manufacturing companies (Basic Industry and Chemical and Consumer Goods Industry Industry) which are listed on the Indonesia Stock Exchange in 2010-2018. Based on the process of sample selection (purposive sampling) 55 companies were obtained so there were 495 observations of research data. There are two research models tested in this study. First, it uses CG and CSR practices as independent variables and company value as the dependent variable. The second uses CG practice as an independent variable and CSR as the dependent variable. In the first model only CSR has a significant effect on the t-sig value of 0,000 (0,000 <0.05). The second model shows that CG has no significant influence on CSR.